Structural steel plate damage detection using non destructive testing, frame energy based statistical features and artificial neural networks - Pandiyan, Paulraj Murugesa , Prof. Dr. (Elsevier Ltd., 2014)
Link to publisher's homepage at http://www.elsevier.com/